Evaluation of performance of various histological grading systems of soft tissue sarcomas and the prognosis (metastatic risk and survival rate) - Baig, Mirza Asif (International Journal of Research in Medical Sciences, 2017)
Background: Histologic grade represents the most important prognostic factor for all soft tissue sarcomas and it is strongly associated with the advent of metastasis and patients survival. The main objective of this study is to test individual grading system with metastatic risk and patients survival rate (prognosis). Methods: Soft tissue sarcomas (250) were graded by FNCLCC, NCI & Mhyre Jensens grading system. Special stains & immunohistochemistry were employed whenever necessary. Results: FNCLCC system shows Grade 1 = 50 (20%), Grade 2 = 75 (30%) & Grade 3 = 125 (50%). NCI (Costa et al.) showed Grade 1 = 70 (28%) Grade 2 = 85 (34%) & Grade 3 = 95 (38%). Myhre Jensen showed Grade 1 = 84 (33%), Grade 98 (39%) & Grade 3 = 68 (27%). Undoubtedly, FNCLCC system is the best of all grading systems which is very well supported by statistical analysis in this study. Conclusions: FNCLCC grading system of soft tissue sarcomas is the best documented and tested system. This present study strongly recommends FNCLCC grading system of soft tissue sarcomas to be internationally accepted because the grading system has well defined criteria & so least possible chances of interobserver variability. The present study & few other previous studies highly recommend the mandatory use of FNCLCC grading system in histopathology report format.